Produção, caracterização e aplicação em biorremediação de bioemulsificante de Acinetobacter venetianus isolada de amostras de petróleo - D’Almeida, Alan Portal (2023)
The application of biological dispersants has been notorious in remediations of oil spills, due to their lower ecotoxicity and greater biodegradability compared to synthetic surfactants, traditionally applied. However, such biomolecules have not been much used industrially due to low yields, the inefficiency of some separation methods and the scarcity of studies of application in bioremediation. In this context, this research seeks to produce, pre-purify, characterize and apply a bioemulsifier of Acinetobacter venetianus, a bacteria isolated from oil of an environmental disaster that hit beaches in the Brazilian Northeast in 2019. To optimize production conditions, the temperature (25-40 ºC), pH (4-10) and NaCl concentration (0-35 g L-1) in the culture medium were varied. Three precipitation methods were also applied: by acid (at pH 2.0, using 12 mol L-1 HCl), by absolute ethanol (2:1 ratio) and by ammonium sulfate (50% m/v). Then the biomolecule was pre-purified by ethanol-salting out method, hot phenol (90% v/v) and extraction with ether. The pre-purified biomolecule was characterized according to its molecular structure by Fourier-transform infrared spectroscopy (FT-IR), mass spectrometry (MALDI-TOF/TOF) and nuclear magnetic resonance (1H NMR). Then, the stability of the crude bioemulsifier was evaluated regarding the presence of NaCl (0 to 50 g L-1), pH (2 to 10) and high temperatures (60 to 120 ºC, for up to 120 minutes). Also, the ecotoxicological characteristics of the biomolecule were studied, measuring the germination index in Ocimum basilicum and Brassica oleracea and the lethal concentration (LC50) in Artemia salina. The bioremediation potential of the emulsifier was evaluated from the decontamination of oil in vitro, on the surface of sea water, and cleaning of sand and rocks. The optimal conditions for the production of crude bioemulsifier were at 30 ºC, in pH 7 medium and supplemented with 3 g L-1 of NaCl, presenting a concentration of 3.3 g L-1 of bioproduct. The ethanol precipitation, the most promising one, increased the emulsification index from 53% (cell-free medium) to 58%, reducing surface tension by 44.4% (40 mN m-1). The pre-purification by the ethanol-salting out method proved to be efficient for the separation of the bioproduct, presenting a critical micellar concentration of 50 mg L-1, and molecular analyzes indicated the production of a bioemulsifier similar to emulsan, with mass of monomeric units of 1099 Da. The crude biosurfactant showed high stability to salinity (up to 50 g L-1), pH (4-8) and temperature variations (up to 120 ºC for 120 min), also presenting low ecotoxicity for plant species (GI% > 80%, at 3000 mg L-1) and microcrustaceans (LC50 of 5750 mg L-1). The bioproduct was able to disperse up to 12% of the oil mass in the marine environment in vitro, mainly C22-C33 hydrocarbons chains, dispersing oil to an area of 50 cm² on the surface of sea water in a total area of 315 cm², removing about 25% of the contaminating oil mass in sand and considerably reducing oil stains adsorbed on rocks. The potential of the strain for the production of bioemulsifiers using diesel oil, hexadecane, kerosene and petroleum as carbon sources was also evaluated, obtaining greater emulsifying activity with kerosene (EI24%: 58%). Supplementation of the medium with hydrophilic carbon sources to increase bioemulsifier production was also studied, in which glucose added to the medium containing kerosene increased the bioemulsifier concentration to 7.5 g L-1. Thus, a bioproduct with high bioremediation potential was produced, presenting promising characteristics for application in several industrial sectors.